Flora of Ceará, Brazil: Simaroubaceae - Ana Brenda Santos Reis; Luana Mateus de Sousa; Francisco Diego Sousa Santos; Maria Iracema Bezerra Loiola (Rodriguésia)
Abstract The aim of this study was to carry out a floristic survey and update the distribution of Simaroubaceae species in the state of Ceará, Brazil, as part of the “Flora of Ceará: from Knowledge to Conservation” project. The descriptions were based on the morphological analysis of samples obtained in the field, in collections deposited in herbaria, consultation of protologs, specialized literature and online database collections. In the state of Ceará, the family is represented by two genera and three species: Homalolepis trichilioides, Simarouba amara and S. versicolor. The three species were recorded in the Lowland Semideciduous Seasonal Forest (Mata de Tabuleiro) and the Steppic Savanna (Caatinga). Simarouba amara and S. versicolor are widely distributed in the state with records also in the Semideciduous Seasonal Forest (Dry Forest) and Vegetation under Rainfall and/or Lake Influence (Riparian Forest). All species were registered in Conservation Units. Identification key, morphological descriptions, comments on ecology, distribution, phenology and uses, maps and illustrations of the species are presented.